Robert C. Bishop, Larry L. Funck, Raymond J. Lewis, Stephen O. Moshier, and John H. Walton, Understanding Scientilc Theories of Origins: Cosmology, Geology, and Biology in Christian Perspective. (6th August 2021) - Ruse, Michael
Abstract : Robert C. Bishop, Larry L. Funck, Raymond J. Lewis, Stephen O. Moshier, and John H. Walton, Understanding Scientilc Theories of Origins: Cosmology, Geology, and Biology in Christian Perspective (Downers Grove, IL: IVP Academic, 2018), xxiv + 659pp., $75.00 (hbk), ISBN: 978-0-8308-5291-8.